Molecular Cloning of Vacuolar H(+)-Pyrophosphatase and Its Developmental Expression in Growing Hypocotyl of Mung Bean - Nakanishi, Yoichi (American Society of Plant Physiologists, 1998)
Vacuolar proton-translocating inorganic pyrophosphatase and H(+)-ATPase acidify the vacuoles and power the vacuolar secondary active transport systems in plants. Developmental changes in the transcription of the pyrophosphatase in growing hypocotyls of mung bean (Vigna radiata) were investigated. The cDNA clone for the mung bean enzyme contains an uninterrupted open reading frame of 2298 bp, coding for a polypeptide of 766 amino acids. Hypocotyls were divided into elongating and mature regions. RNA analysis revealed that the transcript level of the pyrophosphatase was high in the elongating region of the 3-d-old hypocotyl but was extremely low in the mature region of the 5-d-old hypocotyl. The level of transcript of the 68-kD subunit of H(+)-ATPase also decreased after cell maturation. In the elongating region, the proton-pumping activity of pyrophosphatase on the basis of membrane protein was 3 times higher than that of H(+)-ATPase. After cell maturation, the pyrophosphatase activity decreased to 30% of that in the elongating region. The decline in the pyrophosphatase activity was in parallel with a decrease in the enzyme protein content. These findings indicate that the level of the pyrophosphatase, a main vacuolar proton pump in growing cells, is negatively regulated after cell maturation at the transcriptional level.